Enhanced performance of carbon-based supercapacitors by constructing protonic and electric dual-channels in electrodes. (15th January 2019) - Liang, Na; Li, Guoqiang; Ji, Yongsheng; Xu, Jing; Zuo, Danying; Huang, Likun; Zhang, Hongwei
Abstract: Powdery carbonaceous materials have to use binder materials when they are integrated into electrodes for supercapacitors, which will results in high interfacial charge transfer resistances and reduced specific capacitance. To resolve the problem, protonic and electric dual-channels are constructed in electrodes by in situ synthesis of cesium hydrogen salt of phosphotungstic acid on the surface of carbonaceous materials. The cesium hydrogen salt particles are confirmed by a Fourier transform infrared spectroscopy, X-ray diffractometer and an energy dispersive X-ray spectroscopy. The electrochemical properties of as-fabricated electrodes are measured by cyclic voltammetry, galvanostatic charging-discharging, and impedance analysis with an electrochemical workstation. At a current density of 1 A g −1, the electrode shows a specific capacitance of 152 F g −1 . Compared to the electrode without the cesium hydrogen salt, the value increases 25% at least. Furthermore, the specific capacitance retention of the electrode reaches 104% of its original capacitance after 5000 charge-discharge cycles, suggesting excellent cycling stability. Highlights: Protonic and electric dual-channels are constructed in electrodes for EDLCs. The specific capacitance of the EDLC is increased by 25% at least. The specific capacitance retention of the electrode reaches 104% after 5000 cycles.